PERLINDUNGAN HUKUM TERHADAP PERKAWINAN BELUM DICATATKAN BERBASIS MAQASHIDU AL-SYARIAH - Iskak Sulistiya; Absori Absori; Syaifuddin Zuhdi (JOURNAL IURIS SCIENTIA, 2026)
Unregistered marriage remains a family law problem in Indonesia because it creates a gap between religious validity and formal state recognition. This condition has a direct impact on the weak legal protection for women and children, particularly in fulfilling the rights to maintenance, joint property, inheritance, lineage, legal identity, and access to population documents. This study aims to analyze the forms of legal protection for women and children in unregistered marriages and to formulate a construction of legal protection based on Maqashidu al-Syariah. This study employs a normative legal research method with a statutory approach, a conceptual approach, and a maqashidi approach. Legal materials are analyzed qualitatively through descriptive-analytical and prescriptive techniques. The results show that the state has provided several forms of legal protection, namely preventive protection through the obligation of marriage registration, administrative protection through the inclusion of the status "married unregistered" in the Family Card and the use of the Absolute Responsibility Statement, and judicial protection through the marriage ratification (isbat nikah) mechanism. However, this protection is not yet fully effective due to its partial nature. While administrative protection helps fulfill population documents, it does not automatically guarantee the substantive rights of women and children. Therefore, Maqashidu al-Syariah is essential to be used as a basis for the construction of legal protection because it places marriage registration as a means of safeguarding religion, life, lineage, wealth, and family dignity. This study concludes that ideal legal protection must integrate marriage registration, population administration, integrated marriage ratification services, and public legal education to achieve legal certainty, justice, and family welfare.